Формування економіко-організаційного забезпечення реорганізації діяльності промислового підприємства - Александрова, Вікторія Олександрівна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Дисертація на здобуття наукового ступеня кандидата економічних наук за спеціальністю 08.00.04 – економіка та управління підприємствами (за видами економічної діяльності). – Національний технічний університет "Харківський політехнічний інститут". – Харків, 2020. Обґрунтовано сутність дефініції "реорганізація діяльності промислового підприємства". Розроблено теоретико-методичні положення формування організаційно-економічного забезпечення реорганізації діяльності промислових підприємств, що містять: виділення функціональних складових наскрізних бізнес-процесів; формування функціональних зон і організаційних контурів; виокремлення цілей, форм й видів реорганізації діяльності. Проаналізовано фінансовий стан та економічну діяльність суб‘єктів господарювання машинобудівного комплексу України. Сформовано науково-практичні рекомендації щодо визначення факторів впливу на ефективність діяльності промислових підприємств, які передбачають оцінку генерації економічної доданої вартості та імітаційне моделювання закономірностей і взаємозв‘язків показників функціонування та розвитку підприємства. Удосконалено науково-методичний підхід до оцінювання рівнів економічного розвитку та активності, який базується на побудові моделей факторів, які характеризують функціональні зони і організаційні контури реорганізації діяльності промислового підприємства. Розроблено підходи до формування організаційно-економічного забезпечення реорганізації діяльності та прогнозування результатів запровадження важелів реорганізації діяльності промислового підприємства.

The dissertation on achieving a scientific degree of the candidate of economic sciences on a specialty 08.00.04 - economics and management of the enterprises (on kinds of economic activity). - National Technical University "Kharkiv Polytechnic Institute", Kharkiv, 2020. The dissertation is devoted to the development and scientific substantiation of theoretical and scientific-methodical approaches to the development of organizational and economic support for the reorganization of industrial enterprises. The world tendencies of development of mechanical engineering in the world and in the national economy, the basic theoretical approaches concerning the formation of organizational and economic maintenance of carrying out of the reorganization of the industrial enterprise are investigated. Justified the definition of «reorganization of an industrial enterprise» is substantiated, which takes into account the key competencies of the functioning and development of the socio-economic system with the separation of end-to-end business processes to ensure the generation of added economic value. Justified necessity to take into account the functional components (marketing, design, production preparation, procurement and logistics, quality monitoring, product sales, support, and maintenance) of the end-to-end business process, which reflects the implementation of key competencies of the business entity, structural elements (management, main, auxiliary), the formation of functional areas and organizational circuits. The main forms and types of the reorganization of an industrial enterprise are singled out in coordinates: technology, space, time, structure, clients, result, which is the basis for developing methodological approaches to assessment, diagnosis of its financial and economic condition, and formation of reorganization measures. Theoretical and methodological provisions for the formation of organizational and economic support for the reorganization of industrial enterprises, containing: the allocation of functional components of end-to-end business processes; formation of functional zones and organizational contours; identification of goals, forms, and types of the reorganization of activities. The financial condition and economic activity of economic entities of the machine-building complex of Ukraine are analyzed. Scientific and practical recommendations for determining the factors influencing the efficiency of industrial enterprises, which include the assessment of the generation of economic value-added and simulation of patterns and relationships of indicators of operation and development of the enterprise. An improved scientific and methodological approach to assessing the levels of economic development and activity, which is based on the construction of models of factors that characterize the functional areas and organizational contours of the reorganization of the industrial enterprise. The formation of organizational and economic support for the reorganization of the industrial enterprise is based on economic and mathematical modeling and game theory in determining the sets of targeted measures of reorganization by areas and takes into account the relationship and interdependence of their impact on internal and external factors of efficiency. combinations of financial, economic, and organizational tools for the reorganization of the industrial enterprise with certain parameters of influence. The approach to the formation of organizational and economic maintenance of reorganization of activity and forecasting of results of the introduction of levers of the reorganization of activity of the industrial enterprise based on the scenario approach, taking into account restrictions of financial and economic character and definition of the period of achievement of the target level of generation of economic added value is developed. application and implementation in the medium term. The developed proposals are brought to the level of methodical approaches, and their practical implementation in the context of the development of organizational and economic support of the reorganization of industrial enterprises of the Kharkiv region proved their practical significance and expediency of further use of the formed tools.
Formation of economic and organizational support for the reorganization of the industrial enterprise
Keywords: автореферат дисертації; управління підприємствами; реорганізація діяльності промислового підприємства; економіко-організаційне забезпечення; фінансово-економічні результати; реструктуризація підприємства; санація підприємства; наскрізні бізнес-процеси; фінансово-економічні інструменти; фінансово-економічний стан; прогнозування результатів реорганізації; імітаційне моделювання; enterprise management; reorganization of industrial enterprise activity; economic and organizational support; financial and economic results; restructuring of enterprise; rehabilitation of enterprise; through business processes; financial and economic tools; financial and economic condition; forecasting reorganization results; simulation modeling; 330.2